"DREAM JOBS, WORK LIFE BALANCE" (Ustozlar uchun, 2025)
This article explores the issues related to dream jobs and maintaining a healthy work–life balance. The concept of a dream job is defined as a career that matches a person’s interests, skills, and personal values, providing motivation and satisfaction. The article also analyzes how a balanced relationship between work and personal life influences professional development, mental well-being, and productivity. It examines common challenges related to maintaining work–life balance across different professions and discusses strategies for managing them. The article emphasizes the importance of making conscious career choices and establishing a healthy work–life rhythm, especially for young people.